Mass Mortality of Cultivated Northern Bluefin Tuna Thunnus thynnus orientalis Associated With Chattonella Species in Baja California, Mexico - García-Mendoza, Ernesto; Cáceres-Martínez, Jorge; Rivas, David; Fimbres-Martinez, Michelle; Sánchez-Bravo, Yaireb; Vásquez-Yeomans, Rebeca; Medina-Elizalde, Jennifer (Frontiers in Marine Science, 2018)
In 2016 a mass mortality period (MMP) of cage cultured tuna occurred in the northwest coast of Baja California, Mexico. Nine die-offs occurred from May 31st to August 2nd in Todos Santos Bay, Salsipuedes Bay and Coronado Islands. The organisms were disoriented, gasping, swimming erratically and died hours after these signs were detected. Necropsies and histopathological analyses were performed on dead organisms. Abundant mucus and congestion was observed in the gills. Histopathological analysis of the gills showed hyperplasia, fusion of gill filaments and lamellae, telangiectasia, edemas, increased numbers of mucus cells and in some cases severe hemorrhage. Water samples were analyzed and a sampling campaign was implemented in some cultivation areas to evaluate the presence of ichthyotoxic microalgae. Chattonella spp. (mainly C. cf. marina) were detected in the water column during the MMP. At the end of May abundances of 5 x 103 cells L-1 were detected in sea surface samples and Chattonella spp. represented approximately 20% of the microphytoplankton community. Abundance of these species at surface increased to 33 x 103 cells L-1 in June and represented 85% of the phytoplankton community. No other environmental stressful variables were detected during the MMP. The presence of Chattonella spp. in the water column explains the dead of the tuna since behavior, necropsies and histopathological analyses of the gills indicate a severe reaction to an environmental noxa that could be related to the characteristic toxic effect of these species. Before the MMP, ichthyotoxic species have not been reported in the phytoplankton community of the region. Accumulation of Chattonella spp. was probably associated with abnormally high temperatures present during the two previous years before the MMP. Surface temperature anomalies of 3 oC were registered during 2015. Mesoscale oceanographic and atmospheric phenomena brought the environmental conditions for a change in the phytoplankton community in the region. Phytoplankton biomass was low and associated with a decrease in the abundance of diatoms and dinoflagellates. The absence of diatoms together with upwelling events followed by stratification before the MMP probably favored the accumulation of Chattonella spp. that affected importantly tuna ranching activities in Northwest Baja California.